ANALISIS PENGARUH KOMPENSASI DAN KEPEMIMPINAN TERHADAP KINERJA KARYAWAN (Studi pada Karyawan PT. Dharma Agung Electrindo Jakarta) - Tahta Lestari, 09.05.51.0016; Suko Priyono, Bambang (Students Journal of Economic and Management, 2014)
Human resources is on every important factor in a company, in addition to the factors such as capital, one way to improve the performance,motivation and job satisfaction of employees is to provide compensation. Another element in the company of significant value in the enterprise compensation management system is leadership. This research is aimed to examine the effect of variable compensation and leadership to employee performance. Analyses were performed using SPSS. SPSS analysis of the test results showed that compensation shown to significantly affect the performance of employees and leadership proved to have a significant effecton employee performance. Keywords: Compensation, Leadership, Employee Performance